From Satisfaction to Loyalty: A Study of Consumer Behavior in a Trendy Spicy Noodle Outlet - Fernando, Ph.D., Agus (International Journal of Family Business Practices, 2025)
Introduction/Main Objectives: This study examines the factors influencing customer satisfaction and loyalty in a popular spicy noodle restaurant chain in Indonesia. The research focuses on how food quality, perceived value, and pricing affect customer experiences in the competitive quick-service restaurant industry.Background Problems: Despite the chain's rapid expansion, concerns about food quality consistency, hygiene standards, and perceived value have emerged as potential threats to customer retention. This study aims to identify which factors most significantly impact satisfaction and subsequent behavioral intentions.Novelty: This research provides unique insights into consumer behavior in Indonesia's growing quick-service noodle sector, employing an integrated model that connects product attributes with post-purchase behaviors like word-of-mouth and revisit intentions.Research Methods: Using a quantitative approach, data was collected from 237 customers through structured questionnaires. Structural Equation Modeling (SEM) was employed to analyze the relationships between food quality, perceived value, price, satisfaction, word-of-mouth, and revisit intentions.Finding/Results: The analysis reveals that while price significantly affects satisfaction, food quality shows limited impact. Customer satisfaction strongly influences both word-of-mouth recommendations and revisit intentions, with word-of-mouth serving as a key mediator in driving customer loyalty.Conclusion: The findings suggest that restaurant operators should prioritize value perception and pricing strategies over mere food quality improvements. Enhancing overall customer satisfaction appears crucial for generating positive word-of-mouth and encouraging repeat visits in the competitive noodle restaurant market.